The evaluation of the potential of Tenebrio molitor, Zophobas morio, Naophoeta cinerea, Blaptica dubia, Gromphardhina portentosa, Periplaneta americana, Blatta lateralis, Oxyhalao duesta and Hermetia illucens for use in poultry feeds - Hopley, Davina (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.